李渔同性恋作品初探 = An investigation of Li Yu’s works on homosexuality - 王晓亚 Wang, Xiaoya (2016)
Li Yu (1610-1680) is an important writer in the literary history of Late Ming and Early Qing dynasty. My essay mainly describes his three homosexuality works, include Sympathetic to the Female Companion, A MalMencius’Mother taught three moved as well as Cui Ya Building. This works extend Li Yu’s usual style of strange feelings and innovative. In addition, they show many breakthrough of homosexual. Homosexuality is neglected in the heterosexual hegemony society, even the researchers are hardly involved in studying of it. As a relatively open minded but still feudal person, Li Yu showed many sense of paradoxical aesthetic and unconscious heterosexual hegemony in his works. It helps us to understand the blooming of homosexuality in Late Ming and Early Qing dynasty by studying of his articles. At the same time, hope to contribute as a part in today’s discussion of homosexuality rights and equality.